Perspective: What might it cost to reconfigure food systems? - Thornton, Philip K.; Change, Yuling; Loboguerrero Rodriguez, Ana María; Campbell, Bruce M. (Elsevier, 2023)
Even an approximate estimate of the amount of investment required globally to reconfigure food systems for resilience and sustainability in the face of climate change could help to catalyse the urgent action that is needed. A report published in 2020 set out eleven actions that were identified as being needed to reconfigure food systems. Here we estimate the annual cost of implementing these eleven actions to be USD 1.3 ± 0.1 trillion. Half of this is needed to halt conversion of forests and peatlands for agriculture, with the remainder used to reduce producer risk, lower emissions and strengthen the policy, finance and innovation enablers of change. This cost, though large, is equivalent to less than 7 percent of the negative externalities generated annually by current food systems. The costs of inaction will far outweigh the benefits.